2012
DOI: 10.1080/02697459.2012.661194
|View full text |Cite
|
Sign up to set email alerts
|

Framing Cultures of Spatial Planning

Abstract: If one compares different advanced systems of spatial planning, it is surprising that even similar systems show rather different results. This raises the question of what causes these differences. One obvious hypothesis is that in addition to the similarities between planning systems, a number of different 'soft' cultural factors also play a crucial role. Starting from this hypothesis and using an actor-centered approach the article suggests the use of frame analysis as a suitable tool for investigating these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…He goes on to argue that all planning "takes place within a specific institutional context, or often in sets of different and varying "nested" institutional contexts as indeed do all societal activities" ( [31], p. 210). The "institutional embeddedness" of spatial planning endeavors has been acknowledged by many scholars [31][32][33][34]. Nevertheless, the institutional perspective on spatial planning often results in focusing on "planning technologies", i.e., the organizational and institutional structures of spatial planning, such as planning law, administrative structures, procedures and instruments.…”
Section: Institutional Embeddedness Of Spatial Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…He goes on to argue that all planning "takes place within a specific institutional context, or often in sets of different and varying "nested" institutional contexts as indeed do all societal activities" ( [31], p. 210). The "institutional embeddedness" of spatial planning endeavors has been acknowledged by many scholars [31][32][33][34]. Nevertheless, the institutional perspective on spatial planning often results in focusing on "planning technologies", i.e., the organizational and institutional structures of spatial planning, such as planning law, administrative structures, procedures and instruments.…”
Section: Institutional Embeddedness Of Spatial Planningmentioning
confidence: 99%
“…With institutional stability dissolving, planners need to readjust their planning technologies, as well as their basic cognitive frames, "circumscribed as culturally determined frameworks, perspectives, systems of meaning, paradigms or positions from which the actor or a group of actors order social reality and make sense of his or her actions" ( [34], p. 93). Planners are more willing to experiment with new rationales, procedures and instruments, testing new planning technologies in new strategic alliances and networks (phase II).…”
Section: Planning Cultures Between Stability and Changementioning
confidence: 99%
“…(p. 4) So, the cultural perspective is about a society's cultural imprint, meaning the cultural behaviour of all involved actors, different cultural techniques, cultural attitudes and their interaction with each other. In the literature, planning culture is often used with terms like cultural framing (Ernste, 2012), as culturized planning practice (Othengrafen 2010) or planning culture as an underlying concept expressing the practice of planners (Reimer & Blotevogel, 2012, p. 14). Consequently, 'Planning systems and planning practice are part of the culture of a society' (Nuissl, 2008) and the other way round, planning processes produce, develop and maintain the culture of a society by the way in which cities are designed, developed and influenced.…”
Section: Theoretical Derivation Of a Cultural Perspective On Integratmentioning
confidence: 99%
“…The planning context is the central point of departure for actors in the planning processes and their perceptions, interpretations, judgments and actions. For a further analysis of this part of planning culture, compare the already established system-related analysis in spatial planning, where numerous elements of scope are already discussed (Ernste, 2012;Othengrafen, 2012;Reimer & Blotevogel, 2012). Organizational cultures involve all individuals and groups acting on the local, regional or national level.…”
Section: Planning Culture As Analytical Framework For Urban Riverscapesmentioning
confidence: 99%
“…Research papers using the concept can be found in international relations (Schatz and Levine 2010), sociology (Young 2010), spatial planning (Ernste 2012), media and communication studies (Scheufele 1999, Snow, Vliegenthart, and Corrigall-Brown 2007, and many subfields of policy studies (Candel et al 2014, Klüver and Mahoney 2015, Scholten and Van Nispen 2008. Framing has also received enthusiastic attention in the field of interpretive policy analysis (Straus 2010, Van Gorp 2007, Van Hulst and Yanow 2014.…”
Section: Who Stands On Goffman's and Bateson's Shoulders And How?mentioning
confidence: 99%